Enhancement of processed cheese quality using ultrasound: energy density optimization and industrial applications - A. Alsaleem, Khalid (Italian Journal of Food Science, 2024)
This study examined the impact of varying ultrasound energy densities on the functional properties of processed cheese with different levels of emulsifying salt (0%, 0.5%, 1%, 2%, or 3% disodium phosphate). The mixtures were ultrasonicated at 65 watts and 160 watts for either 3 min or 9 min, producing energy densities of 58.5 J/g, 175.5 J/g, 144 J/g, and 432 J/g. The rheological and textural properties of the processed cheese were evaluated at these energy densities and compared to a control sample. At 432 J/g, cheese with 1% emulsifying salt was cooked whereas cheese at 58.5 J/g, 175.5 J/g, and 144 J/g did not cook with the emulsifying salt levels of 1% or lower. There was no significant difference (p > 0.05) in hardness and melting temperature between cheese having the energy density of 432 J/g and processed with 1% and 2% emulsifying salt. Additionally, no significant difference (p > 0.05) was observed in the functional properties of cheese across different energy density treatments. The functional properties of the processed cheese improved significantly with increased emulsifying salt levels. This study suggests that using 432 J/g of ultrasound energy can effectively reduce the requirement of emulsifying salts in the cheese industry.